2021
DOI: 10.32725/kont.2021.019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nurse manager caring behaviors and work environment on burnout syndrome among nurses

Abstract: Nursing is a profession that entails a high risk of burnout, so effective organizational management is needed to reduce its occurrence. This study aims to investigate the moderating effects of Nurse Manager caring behaviors and work environment in burnout syndrome among nurses. This study design uses exploratory descriptions with a cross-sectional approach and considers a sample of 485 nurses in the medical surgical wards at three general hospitals in East Java Province, Indonesia. Data collection was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Gender was not related to burnout (p = 0.86). Research in a government hospital in East Java found similar findings that gender did not deal with burnout (Putra et al, 2021).…”
Section: Relationship Between Burnout and Nurse' Demographic Factorsmentioning
confidence: 75%
See 2 more Smart Citations
“…Gender was not related to burnout (p = 0.86). Research in a government hospital in East Java found similar findings that gender did not deal with burnout (Putra et al, 2021).…”
Section: Relationship Between Burnout and Nurse' Demographic Factorsmentioning
confidence: 75%
“…Burnout symptoms in nurses can be reduced by providing a comfortable work environment. The role of head nurse seems important in managing the workforce functions including planning, scheduling and staff allocation to prevent and reduce burnout symptoms (Putra et al, 2021).…”
Section: Etiology Of Burnout In Nurses In Isolation Roomsmentioning
confidence: 99%
See 1 more Smart Citation
“…They faced difficulties in advocating for professional autonomy or, more specifically, the inclusion of frontline nurses in decision-making processes [ 42 , 43 ]. Scholars have highlighted the need to uphold professional autonomy at work, as nurses with a poorer sense of professional autonomy tended to be more dissatisfied with their job and to experience burnout [ 44 , 45 ]. Regarding team effectiveness, findings of previous research indicated that communication and collaboration could directly impact nurse outcomes, and these were compromised due to the lack of time and increased workload resulting from the pandemic situation [ 6 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 According to Maslach et al 4 , burnout is most common among healthcare workers and is characterized by emotional fatigue, depersonalization and low personal accomplishment impacting behaviors also the work environment. 5 In a study of service personnel, including dentists, burnout was associated with depression, anxiety, alcohol consumption, sleep and cognitive problems and musculoskeletal problems.…”
Section: Introductionmentioning
confidence: 99%